2023
DOI: 10.1021/acs.inorgchem.3c00035
|View full text |Cite
|
Sign up to set email alerts
|

Conformation- and Coordination Mode-Dependent Stimuli-Responsive Salicylaldehyde Hydrazone Zn(II) Complexes

Abstract: Luminescent Zn­(II) complexes that respond to external stimuli are of wide interest due to their potential applications. Schiff base with O,N,O-hydrazone shows excellent luminescence properties with multi-coordination sites for different coordination modes. In this work, three salicylaldehyde hydrazone Zn­(II) complexes (1, 2a, 2b) were synthesized and their stimuli-responsive behaviors in different states were explored. Only complex 1 exhibits reversible and self-recoverable photochromic and photoluminescence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…The HL H ligand was rationally designed to accommodate a metal ion and the mobile H + ion, i.e., it has both the N,N -metal binding site and the O,N -ESIPT site. Such a design strategy allows one to obtain ESIPT-capable metal complexes, an extraordinarily rare class of ESIPT dyes (Scheme , top). ,, , Recently, we synthesized and characterized HL , which differs from HL H by the number and position of CH 3 groups and by the position of hydroxyphenyl and pyrazole substituents to the central pyrimidine core. The reaction of HL with ZnCl 2 in equimolar ratio yielded an ESIPT-capable [Zn­(HL)­Cl 2 ] complex (Scheme , top) .…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The HL H ligand was rationally designed to accommodate a metal ion and the mobile H + ion, i.e., it has both the N,N -metal binding site and the O,N -ESIPT site. Such a design strategy allows one to obtain ESIPT-capable metal complexes, an extraordinarily rare class of ESIPT dyes (Scheme , top). ,, , Recently, we synthesized and characterized HL , which differs from HL H by the number and position of CH 3 groups and by the position of hydroxyphenyl and pyrazole substituents to the central pyrimidine core. The reaction of HL with ZnCl 2 in equimolar ratio yielded an ESIPT-capable [Zn­(HL)­Cl 2 ] complex (Scheme , top) .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Due to the large variety of emissive excited states, the emission of ESIPT-capable molecules is sensitive to various stimuli. The breaking of the intramolecular hydrogen bond due to the interaction of the ESIPT site of the molecule with other molecules or ions or due to deprotonation causes strong changes in the luminescence response of ESIPT-capable molecules. The protonation of ESIPT-capable molecules can proceed at the hydrogen bond-accepting atom switching the ESIPT reaction off or at other heteroatoms leading to modulating ESIPT and ESIPT-coupled luminescence. Binding metal ions by ESIPT dyes which is accompanied by the deprotonation in most cases (only rare examples of ESIPT-capable metal complexes are known) ,, also results in strong changes of emission. This sensitivity allows one to switch the emission of ESIPT-capable molecules between various emission mechanisms and makes them a multivariate platform for the design of stimuli-responsive emissive materials, probes, and sensors.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, these compounds have been found to be an important class of organic materials used as hole-transporting materials [4] or sensors [9]. It has also been shown that acylhydrazones form stable chelate complexes with transition metal cations, using their oxygen and imine nitrogen as donor atoms [10]. Accordingly, additional donor sites (i.e., methoxy groups) can be introduced into their structure to increase the number of coordination sites of the resulting ligand and thus their affinity for metal ions [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Stimuli-responsive materials are promising materials capable of changing one or more of their properties in response to an external stimulus. , Due to their ability to vary their optical characteristics and luminescence in response to mild stimuli (such as vapor exposure, manual grinding, , natural light, etc. ), these materials have caught great interest in the development of environmental sensors.…”
mentioning
confidence: 99%